Anti-T-cell reagents for human bone marrow transplantation: ricin linked to three monoclonal antibodies. - Vallera, D; Ash, R; Zanjani, E; Kersey, J; LeBien, T; Beverley, P; Neville, D; Youle, R (1983)
Three new reagents that react against human T cells were synthesized by covalently linking the toxin ricin to monoclonal antibodies recognizing differentiation antigens on the surface of T lymphocytes. Each of these immunotoxins selectively inhibited T-cell proliferation when the cells were incubated in the presence of lactose. Multipotent human stem cells were inhibited only at much higher concentrations. Mixtures of all three immunotoxins were more effective than any one alone. These reagents have the potential for preventing graft-versus-host disease in man.